The Japanese Journal of Evaluation Studies - John S. Risley (The Evaluation Center at Western Michigan University, 2004)
An analysis of articles in the Japanese Journal of Evaluation Studies published by the Japanese Evaluation Society. The articles are categorized by topic and type.